A Study on Cutaneous Adverse Drug Reactions in ADR Monitoring Centre of Tertiary Care Hospital, Guwahati - Ratan J. Lihite and Mangala Lahkar (Journal of Applied Pharmaceutical Science, 2013)
The observational and cross section study was conducted in the ADR monitoring centre, department of pharmacology, GMCH. The cutaneous adverse drug reactions (CADR) reported by physician of dermatology department of GMCH were collected and then causality, severity and preventability assessment was done. The results were presented as number and percentage. Acne and erythema was commonly reported CADR in our study. Most of the reported CADRs were possible, definitely preventable and mild in nature. Our study suggests that there is a need of intensive monitoring for ADRs in tertiary care hospital for early detection and to ensure the patient safety.
Keywords: CADRs, ADR monitoring centre, causality, severity.&l